Exploring Multicultural Identity A Gynocritical Study of Kingston’s The Woman Warrior - Ismail, Hana Shoresh; Arif, Kawan Osman (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
This paper aims to establish and identify what is taken to be the distinctively feminine subject matters in The Woman warrior: Memoirs of a Girlhood Among Ghosts which is a book written by the Chinese American author Maxine Hong Kingston from a multicultural perspective. Furthermore, it is to uncover in literary history a female tradition to show that there is a distinctive feminine mode of experience, or subjectivity, in thinking, valuing, and perceiving oneself and the outer world. Its main concern is to see woman as producer of genres and structures of literature. It also examines how gender, culture, family and traditions interact and transmit cultural effects on the self and identity. The major characters in The Woman Warrior such as the author, the mother Brave Orchid, and the auntie Moon Orchid, live in a Chinese ethnic community isolated from the conventional society. Moreover, to a great extent gendered experience of the female major characters is characterized by ethnic identity as well. The applied methodology in this paper is a feminist gynocritical approach. Gynocriticism is the examination of female writers and their place in literary history and the discovery and exploration of a canon of literature written by women. The paper ends up with conclusions and a list of works cited.